Domestic Wind Energy Planning for Deprived Communities in the Tropics: A Case Study of Nigeria - Moses Eterigho Emetere; Omoremime Elizabeth Dania; Sunday Adeniran Afolalu (International Journal of Renewable Energy Development, 2023)
Despite the notable inventions in solar energy, it is still too high for standalone users from developing countries. For example, it cost $2200 to provide power for a two-bedroom apartment while the average citizen lives below the country’s poverty line of $381.75 per year. The use of fossil fuel generators remains cheaper, except there is an affordable energy option for the average populace. The objective of this study is to investigate the wind energy potential for domestic or standalone use in Nigeria. It is proposed that the domestic wind turbine will be relatively cheap for adoption. Hence, there is the need to wholistic examine the prospects of wind energy generation in Nigeria. Though previous studies had been carried out, none has been wholistic as presented in this research work. Forty years wind speed and wind direction dataset, i.e., 1980-2020, was obtained from the Modern-Era Retrospective analysis for Research and Applications (MERRA). The analysis of the wind energy potential across the research locations was considered using five sampling techniques, i.e., considering the general statistics of the forty years dataset; considering ten years in an evenly distributed pattern and accruable wind energy across the nation. It was observed that the early wet season (MAM) is the most unstable among the seasons. Also, sudden multi-directionality of the wind vectorization within forty years was observed. This event is ascribed to evidence of climate change to wind energy generation. Wind energy generation prospect was seen to be generally sustainable and reliable with SON, MAM, DJF and JJA having energy distribution of 325-950 kWh, 539-1700 kWh, 161-650 kWh and 761-3650 kWh respectively. Despite the variation of energy generation over the years within all seasons over Nigeria, it was found that it is predictable and can be optimized using various technological solutions.